2013
DOI: 10.1016/j.jbo.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of macrophages in bone metastasis

Abstract: The skeleton is one of the most common sites of metastatic disease, affecting a large number of patients with advanced cancer. Although an increasing number of therapies are available for treatment of bone metastasis, this remains incurable, highlighting the need for better understanding of the underlying biology. Metastatic tumour spread to distant organs is a multistage process, involving not only cancer cells but also those of the surrounding host microenvironment. Tumour associated macrophages are multifun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 74 publications
(122 reference statements)
1
20
0
Order By: Relevance
“…Unlike cancer cells, FR-β expression on stromal cells correlated positively with cancer stage and the closely related category of lymph node involvement ( p -values of 0.0212 and 0.0293, respectively), even though none of the groups were significantly different from one another (Figure 5B ). While the mechanistic underpinnings of this correlation still need to be explored, it has been established for some time that tumor-associated macrophages greatly increase the invasiveness and metastatic potential of tumors [ 33 , 34 , 35 ]. Because the tumor associated macrophages in this study were strongly FR-β positive, as reported previously for melanoma, pancreatic and head and neck cancers [ 9 , 10 , 23 ], the correlation with cancer stage and lymph node involvement suggests the intriguing possibility that FR-β might not only constitute a useful indicator of tumor metastatic potential, but may also serve as an attractive target for folate-mediated delivery of drugs for reprogramming the tumor's immune environment.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike cancer cells, FR-β expression on stromal cells correlated positively with cancer stage and the closely related category of lymph node involvement ( p -values of 0.0212 and 0.0293, respectively), even though none of the groups were significantly different from one another (Figure 5B ). While the mechanistic underpinnings of this correlation still need to be explored, it has been established for some time that tumor-associated macrophages greatly increase the invasiveness and metastatic potential of tumors [ 33 , 34 , 35 ]. Because the tumor associated macrophages in this study were strongly FR-β positive, as reported previously for melanoma, pancreatic and head and neck cancers [ 9 , 10 , 23 ], the correlation with cancer stage and lymph node involvement suggests the intriguing possibility that FR-β might not only constitute a useful indicator of tumor metastatic potential, but may also serve as an attractive target for folate-mediated delivery of drugs for reprogramming the tumor's immune environment.…”
Section: Resultsmentioning
confidence: 99%
“…First, TAMs contribute to angiogenesis [22], a process detailing the formation of new blood vessels from pre-existing blood vessels. For example, production of IL-1β by TAMs induces expression of HIF-1 by the tumour cells [27]. An increase in TAM numbers correlates with an increase in tumour angiogenesis.…”
Section: Role Of Inflammatory Cells In Oncogenesismentioning
confidence: 99%
“…An increase in TAM numbers correlates with an increase in tumour angiogenesis. Factors such as IL-10, PGE 2 (prostaglandin E 2 ), and TGFβ1 expressed by TAMs can contribute to decreased IL-12 expression, thereby suppressing both T-cell and NK (natural killer) cell proliferation and their associated cytotoxic effects [27]. For example, production of IL-1β by TAMs induces expression of HIF-1 by the tumour cells [27].…”
Section: Role Of Inflammatory Cells In Oncogenesismentioning
confidence: 99%
“…Classical activation of macrophages and development of classically activated macrophages from monocytes evoke increased pro-inflammatory cytokine secretion and this M1 activation can be facilitated by exposure of macrophages to LPS and IFN [103,104].…”
Section: Macrophage Modulatorsmentioning
confidence: 99%
“…Alternative activation of macrophages elicits anti-inflammatory responses from macrophages and this M2 activation is achieved by exposing macrophages to IL-4 or IL-13 [103,104] Apart from these stimuli, macrophage modulation can also be brought about by epigenetic modifications, which are discussed in the next section.…”
Section: Macrophage Modulatorsmentioning
confidence: 99%